Effect of an educational pamphlet on the awareness of parents of primary school children about dento-facial characteristics: Mashhad, Iran - Maryam Omidkhoda; Mahsa Shahrokh; Shahla Momeni Danaei; Mahboobe Dehghani (Mashhad University of Medical Sciences, 2023)
Background: Today, dental emphasis has been placed on prevention. The pamphlet is a great tool for conveying information and raising awareness. In this study, the aim was to determine the effectiveness of an educational pamphlet on parents' awareness of the dental problems of primary school children in Mashhad, Iran.Method: 601 parents of primary school children were selected by random clustering method from primary schools in 7 districts of Mashhad. In each training area, a girls 'primary school for the interventional group and a girls' school for the control group entered the study.In the first session, Questionnaire 1 was delivered to parents of children and they were asked to complete the questionnaire. Then in the intervention groups, the educational pamphlets were delivered to the parents. One month after the delivery of the pamphlet, during the second session, Questionnaire 2 was completed again by the same group and scored, and the score was recorded before and after the intervention for the parents. In the control group, the training pamphlet was delivered during the second session after filling out questionnaire2.Results: In the first assessment, two groups had no significant difference in awareness level (P=0.537), but they showed significant difference after second evaluation (P<0.001). The parents' awareness score in the second questionnaire increased by 6.10 times in the intervention group and 0.834 times in the control group.Conclusion: According to the results, pamphlets are a good tool to increase parental dento-facial awareness.